How anesthetists manage growing demands with dwindling resources in German university hospitals: Overview and outlook. Issue 1 (March 2018) - Hinkelmann, Juergen; Hasebrook, Joachim; Goeters, Christiane; Hahnenkamp, Klaus
Abstract : As a central service provider in medical care, anesthetists manage the growing demand on medical services, thereby increasing specialization and patient morbidity. Various indicators and measurements have been used to match staff capacity, competence, and workload. It remains unclear whether the problems are due to real shortages or "just" to a wrong distribution. Medical services, service development, infrastructure, capacity, and competences of medical staff of 15 departments of anesthesiology at German university hospitals were compared. They reported an increase in medical service and staff capacity. Competences did not grow, fluctuation rates were high, and part-time employment increased. The broad variety of hospitals' infrastructures requires different staff capacity and competence structures. Anesthetists need to take on a key role in redesigning hospital performance and staff management to ensure performance increases, patient safety, and bearable workloads. Optimal distribution of expertise and early counteraction for shortages in staff capacities and competences is needed.